(untitled) (Butwal Campus Journal, 2023)
The main objective of this study is to investigate key elements for effectively implementing inclusive education in schools in Nepal. A qualitative phenomenological research design has been applied to investigate the problem. Three community schools with resource classes were purposively selected as a representative sample from the districts of Rupandehi, Nawalparasi and Kavre. Interviews and focus group discussions served as the research tools for data collection. A semi-structured interview schedule was developed and utilized for the head teachers and resource teachers; whereas, questions for focus group discussion were developed and administered to the teachers of sample schools. The collected data were transcribed, grouped and categorized for their analysis. The findings reveal that several key elements are important for the smooth execution of inclusive education in Nepalese schools. These elements include disabled-friendly infrastructure; curriculum, teaching strategies and assessment; inclusive school leadership; implementable policies and legal instruments; trained teachers; active involvement of parents and community; positive attitude of teachers and peers; and adequate financing.